A Simple Ultrasound Score for the Accurate Detection of Inflammatory Activity in Crohn's Disease. Issue 11 (November 2017) - Novak, Kerri L.; Kaplan, Gilaad G.; Panaccione, Remo; Afshar, Elnaz Ehteshami; Tanyingoh, Divine; Swain, Mark; Kellar, Amelia; Wilson, Stephanie
Abstract : Background: Ultrasound is accurate in the detection of Crohn's disease. Our aim was to identify ultrasound parameters contributing to inflammatory disease activity, develop a simple score, and validate this score prospectively. Methods: This study comprised 2 single-center investigations. The first was a retrospective study on a population that had received colonoscopies (as a gold-standard diagnostic) within 60 days of ultrasound. The second was a prospective study on 2 populations: patients requiring induction with adalimumab and patients on adalimumab maintenance therapy. Ultrasound and endoscopy were preformed within 14 days in both prospective groups. The endoscopy results were graded with the Simple Endoscopic Score and the Rutgeerts score and compared with 5 ultrasound parameters. We used a proportional odds model to determine which ultrasound parameters correlated significantly with the endoscopy results. We then developed a predictive ultrasound score for disease activity, plotted the receiver operating characteristic curves, and undertook prospective validation of the score. Results: We evaluated 160 patients retrospectively to compare ultrasound and colonoscopy. Two of 5 parameters were found to correlate significantly with disease activity: bowel wall thickness ( P = <0.0001) and color Doppler signal ( P = 0.0292). We developed a score that uses weighted variables. The area under the corresponding receiver operating characteristic curve was 0.8658. Conclusions: A simple ultrasonographic score that accurately identifies Crohn's disease activity has been developed and validated. Ultrasound may be a surrogate for endoscopy to guide disease management, but future studies should be conducted to establish interrater variability. Abstract : Article first published online 20 June 2017.